Motivasi Eksistensi Pekerja Informal Sukarelawan Pengatur Lalu Lintas (Supeltas) di jakarta, Bogor dan Bekasi - Mochamad Sarif Hasyim; Raissa Indrasari Romadhona; Imanda Putri (Multiverse: Open Multidisciplinary Journal, 2022)
The presence of traffic control volunteers (Supeltas) plays an quite important role in public order and smooth traffic. The research was conducted in the cities of Jakarta, Bogor and Bekasi. In these three places it is known that there are problems that are troubling the community such as traffic jams. The congestion is caused by the large volume of motorized vehicles that are not proportional to the volume or number of roads, especially on lanes that have a very large potential to cause a buildup of vehicles such as at intersections or U-turns. The presence of traffic control volunteers (supeltas) appears at these locations in almost all corners of the city taking over the role of the traffic control police. The existence of traffic control volunteers has been going on for a long time, so it is very interesting to do research on the motivation of these informal workers. The method used in this study uses a descriptive qualitative approach. The results of this study indicate that the motivation to become a traffic control volunteer (supeltas) is a desire to help smooth traffic due to congestion and the convenience of road users, but it cannot be denied that the existence of traffic control volunteers has become a livelihood. The contribution of the existence of the informal sector in overcoming various employment problems in Indonesia requires efforts to provide continuous guidance. Guidance can be carried out mainly by the government, private institutions and independent community groups who care about social problems in society